The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.26522/ssj.v4i2.999
|View full text |Cite
|
Sign up to set email alerts
|

The Advocate’s Dilemma: Framing Migrant Rights in National Settings

Abstract: This article identifies and explores the dilemma of migrant advocacy in advanced industrial democracies, focusing specifically on the contemporary United States. On the one hand, universal norms such as human rights, which are theoretically well suited to advancing migrants' claims, may have little resonance within national settings. On the other hand, the debates around which immigration arguments typically turn, and the terrain on which advocates must fight, derive their values and assumptions from a nation-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 29 publications
(20 reference statements)
0
14
0
Order By: Relevance
“…My project focuses on the discursive framing process, defined as 'conscious strategic efforts by groups of people to fashion shared understandings of the world and of themselves that legitimate and motivate collective action' (Keck andSikkink 1998, Snow andBenford 1988). 4 Based on inductive analysis of NOII Toronto's DADT campaign, I identified NOII's use of a human rights framing as a central discursive strategy deployed by movement activists in order to mobilize a broad range of constituents and garner national media attention; this finding is supported by recent research that cites the intentional use of human rights discourse by NOII and other 'no borders' movements to bolster claims against the state (Basok 2009, Cook 2010, Grugel and Piper 2011. Social movement scholars have examined the usefulness of human rights frames for mobilizing a broad range of constituents across varying cultural and political contexts, thereby bolstering efforts to hold states accountable (Keck and Sikkink 1998, Jenness and Grattet 2001, Grugel and Piper 2011.…”
Section: S Abji 326mentioning
confidence: 95%
See 1 more Smart Citation
“…My project focuses on the discursive framing process, defined as 'conscious strategic efforts by groups of people to fashion shared understandings of the world and of themselves that legitimate and motivate collective action' (Keck andSikkink 1998, Snow andBenford 1988). 4 Based on inductive analysis of NOII Toronto's DADT campaign, I identified NOII's use of a human rights framing as a central discursive strategy deployed by movement activists in order to mobilize a broad range of constituents and garner national media attention; this finding is supported by recent research that cites the intentional use of human rights discourse by NOII and other 'no borders' movements to bolster claims against the state (Basok 2009, Cook 2010, Grugel and Piper 2011. Social movement scholars have examined the usefulness of human rights frames for mobilizing a broad range of constituents across varying cultural and political contexts, thereby bolstering efforts to hold states accountable (Keck and Sikkink 1998, Jenness and Grattet 2001, Grugel and Piper 2011.…”
Section: S Abji 326mentioning
confidence: 95%
“…More recently, scholars examining NOII and other 'no borders' movements have begun to highlight the tensions and opportunities involved for these movements in making claims against the state (McDonald 2007, Racine et al 2008, Basok 2009, Cook 2010, Fortier 2010, Nyers 2010. For example, Cook shows how human rights frames used within national immigration debates in the USA (as opposed to transnational or international debates) still have relatively little resonance compared with the use of state-centred frames in shifting public opinion; yet, the use of state-centred frames is self-limiting, in that they may reinforce the values and assumptions that produce immigration restrictions in the first place -a challenge coined the 'advocate's dilemma' (2010).…”
Section: S Abji 326mentioning
confidence: 99%
“…This approach represents a common 'dilemma of migrant advocacy in advanced industrial democracies, where a more universal conception of immigrant rights based in human rights has little resonance (Cook 2010). As such, a large emphasis is placed on the constitutional protections afforded to immigrants, as was the case in the wake of Arizona's controversial Senate Bill 1070.…”
Section: The Landscape Of Immigrant Rights Framesmentioning
confidence: 99%
“…To do so, it focuses on the work of domestic CSOs engaging with policy debates about refugee and asylum rights in the United Kingdom. This is a particularly useful example because previous studies have found that these organisations face significant challenges in navigating policy debates which are largely hostile to their views (Cook, 2010;Cullen, 2009;McGhee et al, 2016;Somerville and Wallace Goodman, 2010;Statham and Geddes, 2006).The article presents an analysis of research into the 'policy narratives' of seven case study organisations working in the UK to explore how these challenges shape the organisations' interventions into policy debates in the UK field and, consequently, how they position themselves as policy actors.…”
Section: Introductionmentioning
confidence: 99%